Factors Influencing Economic Development in Mogadishu, Somalia - Osman, Abdinasir Aden; Kavale, Stanley (International Journal For Research In Agricultural And Food Science, 2018)
Despite the numerous strategies implemented to increase economic development in somalia, no break through yet. The study aimed at investigating the factors influencing economic development of Somalia. The study was guided by the following objectives; to find out the effect of government spending on economic development of Mogadishu, Somalia, to find out the effect of saving on economic development of Mogadishu, Somalia, to find out the effect of investment on economic development of Mogadishu, Somalia. Descriptive research design was used with a target population of 134 and a sample size of 100 respondents from. Data was collected and analyzed using Statistical Package for the Social Sciences (SPSS) version 21. From the analysis it was found out that there is a significant effect of government spending, investment and savings on economic development. The study recommended that the government of Somalia should increase government spending, increase investment in health, education, infrastructure and encourage bank and house hold savings.